Burden of Respiratory Syncytial Virus Infection in South African Human Immunodeficiency Virus (HIV)-Infected and HIV-Uninfected Pregnant and Postpartum Women: A Longitudinal Cohort Study - Madhi, Shabir A (Clin Infect Dis, 2018)
BACKGROUND: Limited data exist on the burden of respiratory syncytial virus (RSV) illness among pregnant women, to determine their potential benefit from RSV vaccination. We evaluated the incidence of RSV illness from midpregnancy until 24 weeks postpartum in human immunodeficiency virus (HIV)–uninfected and HIV-infected women and their infants. METHODS: Mother–infant dyads were enrolled in maternal influenza vaccine efficacy trials. These included 1060 and 1056 HIV-uninfected pregnant women in 2011 and 2012, respectively, 194 HIV-infected pregnant women in 2011, and their infants. Upper respiratory tract samples obtained at illness visits were tested for RSV. RESULTS: The incidence (per 1000 person-months) of RSV illness (n = 43 overall) among HIV-uninfected women was lower in 2011 (1.2; 95% confidence interval [CI], .6–2.2) than in 2012 (4.0; 95% CI, 2.8–5.6). The incidence of RSV illness (n = 5) in HIV-infected women was 3.4 (95% CI, 1.4–8.1). Maternal RSV infection was associated with respiratory symptoms including cough (72.1%), rhinorrhea (39.5%), sore throat (37.2%), and headache (42%), but fever was absent. RSV infection during pregnancy was not associated with adverse pregnancy outcomes. Postpartum, RSV infection in mothers (n = 27) was associated with concurrent infection among 51.9% of their infants and, conversely, 29.8% of mothers investigated within 7 days of their infants having an RSV illness also tested positive for RSV. CONCLUSIONS: RSV infection is associated with respiratory illness during pregnancy and postpartum. Vaccination of pregnant women against RSV could benefit the mother, albeit primarily against nonfebrile illness, and her infant. CLINICAL TRIAL REGISTRATION: NCT01306669 and NCT01306682.